Interplay among Pseudomonas syringae HrpR, HrpS and HrpV proteins for regulation of the type III secretion system. Issue 2 (19th June 2014) - Jovanovic, Milija; Lawton, Edward; Schumacher, Jörg; Buck, Martin
Abstract Pseudomonas syringae pv. tomato DC3000, a plant pathogenic gram‐negative bacterium, employs the type III secretion system (T3SS) to cause disease in tomato and Arabidopsis and to induce the hypersensitive response in nonhost plants. The expression of T3SS is regulated by the HrpL extracytoplasmic sigma factor. Expression of HrpL is controlled by transcriptional activators HrpR and HrpS and negative regulator HrpV. In this study, we analysed the organization of HrpRS and HrpV regulatory proteins and interplay between them. We identified one key residue I26 in HrpS required for repression by HrpV. Substitution of I26 in HrpS abolishes its interaction with HrpV and impairs interactions between HrpS and HrpR and the self‐association of HrpS. We show that HrpS self‐associates and can associate simultaneously with HrpR and HrpV. We now propose that HrpS has a central role in the assembly of the regulatory HrpRSV complex. Deletion analysis of HrpR and HrpS proteins showed that C‐terminal parts of HrpR and HrpS confer determinants indispensable for their self‐assembly.